A genetic and morphological investigation of the forces shaping the diversity and distribution of the Eurasian red squirrel, Sciurus vulgaris - Finnegan, Laura A. (Trinity College (Dublin, Ireland). Department of Zoology, 2007)
An understanding of the factors which shape the range of, and distribution of diversity within, a species, is fundamental in understanding both the species itself, but also, the effectiveness, if needed, of conservation measures. The Eurasian red squirrel, Sciurus vulgaris, is one of the most widely studied of the Scuiridae, however research into the effects of historical, geographical and local factors which are instrumental in shaping the diversity of the species are scarce. As well as increasing understanding of the species, this information will be critical in designing conservation strategies in the face of ongoing replacement of the red squirrel in the British Isles and Italy, and possibly in the future mainland Europe, by the introduced American grey squirrel, Sciurus carolinensis.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin